2015
DOI: 10.1589/jpts.27.3417
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different imitation models on theaccuracy and speed of imitation of movement

Abstract: [Purpose] The purpose of this study was to compare the accuracy, speed and subjective ease of imitation of movement using three different imitation models. [Subjects] Thirty-four right-handed healthy males participated in this study. [Methods] The imitation task chosen for this study was an asymmetric combined motion of the upper and lower limbs. Three kinds of imitation models were displayed on a screen as follows: a) third person perspective mirror imitation (3PM), b) third person perspective anatomical imit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…These findings are in accordance with those of previous studies regarding imitative behavior, which have reported that simple finger-tapping or finger-lifting tasks produced no positive effects on behavior in the FPP condition relative to the TPP condition [Ramenzoni et al, 2015;Watanabe et al, 2013]. In contrast, Nishizawa et al [2015] utilized a task in which participants were required to imitate whole-body movements, reporting significant positive behavioral effects in the FPP relative to the TPP (i.e., lower error rates). Such findings suggest that the behavioral effects of the FPP during imitative conditions are modulated by the degree of dynamicity of the performer's action [Nishizawa et al, 2015;Ramenzoni et al, 2015].…”
Section: Table V Correlational Analysis (Parametric Modulation Analysupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in accordance with those of previous studies regarding imitative behavior, which have reported that simple finger-tapping or finger-lifting tasks produced no positive effects on behavior in the FPP condition relative to the TPP condition [Ramenzoni et al, 2015;Watanabe et al, 2013]. In contrast, Nishizawa et al [2015] utilized a task in which participants were required to imitate whole-body movements, reporting significant positive behavioral effects in the FPP relative to the TPP (i.e., lower error rates). Such findings suggest that the behavioral effects of the FPP during imitative conditions are modulated by the degree of dynamicity of the performer's action [Nishizawa et al, 2015;Ramenzoni et al, 2015].…”
Section: Table V Correlational Analysis (Parametric Modulation Analysupporting
confidence: 91%
“…Previous studies have indicated that movements presented from the first-person perspective (FPP; i.e., observing the movement as if one were executing it) are more effective in guiding imitative behavior than those presented from the third-person perspective (TPP; i.e., observing the movement as if one were looking at it in a mirror) [Jackson et al, 2006;Nishizawa et al, 2015;Ramenzoni et al, 2015;Vogt et al, 2003;Watanabe and Higuchi, 2016]. In addition, previous imaging studies of imitative behavior have demonstrated that the mirror neuron system (MNS)-which includes the ventral premotor area (PMv), inferior frontal gyrus (IFG), and inferior parietal lobule (IPL)-and the posterior superior temporal sulcus (pSTS) are more active when body movements are presented from the FPP than from the TPP [Alaerts et al, 2009;Jackson et al, 2006;Oosterhof et al, 2012;Vingerhoets et al, 2012;Vogeley and Fink, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Several imitation studies have reported that sensory information available from the first-person POV, as if the imitator were observing the model from his/her own perspective, is greater than that viewed from the third-person perspective, where the model is facing the observer [21][22][23] . The first-person perspective model facilitates more accurate imitative behavior than the third-person perspective model 24,25 and it induces greater activity in the mirror neuron system (MNS), which is implicated in the processing of visuomotor information 26,27 . Differently, studies investigating the first and third-person through videogames, have highlighted that the playing view influences the presence of emotional responses 28 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Tool for rating: self-assessment manikin. According to Russell & Barrett 24 , each emotion arises from the linear combination of valence and arousal. The valence dimension indicates whether the observer likes or dislikes an event, an object, or a situation.…”
Section: Background and Summarymentioning
confidence: 99%
“…Several imitation studies have reported that sensory information available from the first-person perspective (i.e., as if the imitator were observing the model from his/her own perspective) is greater than that viewed from the third-person perspective (i.e., with the model facing the observer; Vogt et al, 2003 ; Jackson et al, 2006 ; Oosterhof et al, 2012 ). The first-person perspective model facilitates more accurate imitative behavior than does the third-person perspective model ( Jackson et al, 2006 ; Nishizawa et al, 2015 ; Ramenzoni et al, 2015 ) and induces greater activity in the mirror neuron system (MNS), which is implicated in the processing of visuomotor information ( Watanabe et al, 2013 ). As shown by action observation studies, the first-person perspective visually transfers motor information from the models to observers ( Alaerts et al, 2009 ; Wakita and Hiraishi, 2011 ), allowing observers to respond quickly and appropriately during a task ( Bortoletto et al, 2013 ; Bach et al, 2014 ; Brattan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%